Construction of Scale to Measure Women Farmers’ Attitude towards Climate Resilient Dairy Farming Practices - Reddy, Dadimi Anil Kumar; Garai, Sanchita; Maiti, Sanjit; Manjunath, K V; Panja, Amitava; Sahani, Shravani (Indian Journal of Extension Education, 2023)
Understanding farmers’ attitude is instrumental in initiating/formulating any strategy to promote the adoption of technology. A scale was developed to analyze the attitude of women farmers towards climate-resilient dairy farming practices. A list of 50 statements comprising both positive and negative statements were collated and refined based on Edward’s 14 principles and 35 statements were retained for administering to women farmers from non-sampling area for further analysis. Finally, “t” value for each statement, and found that 17 statements were having “t” value greater than 1.75. The 17 statements were rained for the final scale and administered for reliability and validity testing. Cronbach alpha coefficient of 0.786 confirmed the internal consistency of the developed scale. The content validity of the scale was ascertained based on the judgment of the experts. The final developed scale can be used to measure the attitude of women farmers on climate-resilient dairy farming practices in the present context and beyond the study area with modifications.
Keywords: Attitude; Scale; Climate resilient dairy farming practices; Women dairy farmers